Exploring the Maturity of Smart Public Governance: Evidence from Two Policy Sectors in Slovenia - Vujković, Petra; Jukić, Tina (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
This paper applies a case study approach to test a multi-attribute decision-support model for assessing smart public governance maturity in real-life settings. Developed on prior research, verified through synthetic cases, and validated through expert focus group discussions, the model enables a structured, criteria-based assessment of smart public governance maturity across four dimensions: ICT-enabled innovations for public sector governance, institutional changes, empowered citizens, and outcomes: public value creation. Two public administration organisations in charge of policy making in Slovenia, each operating in a distinct policy sector, were used as case studies for testing the proposed assessment tool. Data were collected through semi-structured interviews with policy makers, and responses were aligned with predefined attribute value scales. The findings confirm that the model can be applied in practice as a useful tool for public sector organisations seeking to assess their smart public governance maturity level and identify areas for further improvement.